Synopsis of the family Reduviidae (Heteroptera: Cimicomorpha) from Chile - Melo, María Cecilia (2015)
A synopsis of the Reduviidae recorded from Chile is given, including keys to subfamilies, genera, and species, as well as new distributional records. A total of seven subfamilies, 17 genera, and 27 species are here recorded, one represents a new country record: Leogorrus litura (Fabricius); there are also included many distributional data as well as extensions of the ranges of several species.